Advanced Patient-Centered Communication for Health Behavior Change: Motivational Interviewing Workshops for Medical Learners - Kathryn Brogan Hartlieb; Brett Engle; Vivian Obeso; Maryse A. Pedoussaut; Lisa J. Merlo; David R. Brown (Association of American Medical Colleges, 2016)
Abstract Introduction Medical settings are critical access points for behavior change counseling, and lifestyle behavior change is considered a key component of chronic disease management. The Association of American Medical Colleges recommends that future physicians be competent in shared decision making and patient-centered behavioral guidance to prevent illness and improve patient self-management of chronic disease. Motivational interviewing (MI) is a patient-centered, directive method of communication to enhance behavior change. Specific teachable strategies underlie the collaborative MI communication style that aims to reduce discord and build motivation for change. Methods We present our three-session 12-hour MI curriculum as an advanced form of patient-centered communication. Each session includes presession assignment, large-group interactive lecture, and small-group activities for practice. An interdisciplinary team consisting of medical educators and health behavior change research-educators who are also members of the Motivational Interviewing Network of Trainers created the submission. The purpose of this resource is to provide medical educators with a short curriculum that incorporates materials and learning activities to promote skill in MI. Results In addition to positive feedback from student evaluations including the areas of relevance to training and self-rated skills improvement, preliminary pre- and posttraining scores from the medical students show significant improvement in expression of empathy and the ratio of reflections to questions. Discussion Implementation of the curriculum allows learners the opportunity to practice evidence-based communication that promotes intrinsic motivation for health behavior change in patients, a key treatment focus in chronic disease management.